Concurrent Alcohol Use and Waterpipe Tobacco Smoking: Smoking Topography, Toxicant Exposure, and Abuse Liability. Issue 2 (1st March 2019) - Leavens, Eleanor L S; Morgan, Taylor L; Brett, Emma I; Patzkowsky, Kelsey; Son, Jessica; Molina, Neil; Eissenberg, Thomas; Shihadeh, Alan; Leffingwell, Thad R; Wagener, Theodore L
Abstract: Introduction: Relative to non-waterpipe (WP) smokers, WP smokers are more than twice as likely to use alcohol and frequently consume alcohol before or during smoking sessions. Co-use of alcohol and WP may result in greater toxicant exposure compared to WP smoking alone. To date, no study systematically has investigated the impact of acute alcohol intoxication on WP smoking topography, exposure to tobacco-related toxicants, or abuse liability. Methods: Dyads of current WP smokers and drinkers (N = 42; age = 21–32 years) completed two in-laboratory ad libitum smoking sessions (≤2 hours) following 12-hour nicotine abstinence in a double-blind, randomized crossover design in which they consumed a placebo versus active drink (sustained breath alcohol concentration = .08). Exhaled carbon monoxide (eCO) and plasma nicotine concentration were assessed. Questionnaires assessed smoking experience and smoking urge. Smoking topography was measured continuously throughout each smoking session. Results: The alcohol session was associated with increased inhaled volume, flow rate, and WP session duration compared to placebo. Compared to placebo, participants reported a more positive overall smoking experience following the alcohol session and greater smoking urges pre- and post-smoking session. Although both sessions resulted in significant increases in eCO and plasma nicotine, no significant differences emerged in eCO or nicotine exposure between the active and placebo sessions. Conclusions: Co-use of alcohol and WP may contribute to the maintenance of WP smoking through enhanced smoking experiences, increased urge to smoke, and significant exposure to addictive nicotine. Regulations may be necessary to limit the sale of alcohol in WP smoking lounges and reduce exposure to secondhand smoke. Implications: The findings suggest co-use of alcohol and WP tobacco likely maintain WP use and dependence by enhancing the smoking experience and increasing urges to smoke. These findings have implications for regulations aimed at limiting co-use of alcohol and WP tobacco in WP lounges and limiting exposure to secondhand smoke. Clinical trials registration: NCT03096860